The Effectiveness of Providing Counseling in Efforts do Improve Knowledge and Dietary Patterns of Low Purine Diet in Gout Arthritis Patients at Bintang Bayu Health Center Serdang Bedagai - Damayanti, Erika; Harris Rambey; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Gout arthritis is one of the non-communicable diseases that commonly affects the elderly due to a high-purine diet and lack of nutritional knowledge. This study aims to determine the effectiveness of counseling in increasing knowledge and low-purine dietary patterns in patients with gout arthritis. This study used a mixed-methods approach with a one-group pretest-posttest research design. The sample consisted of 22 elderly patients with gout arthritis at Puskesmas Bintang Bayu. Data were collected through a knowledge questionnaire, 24-hour food recall, and in-depth interviews. The results showed a significant increase in the level of knowledge (p=0.001) and dietary patterns after the counseling intervention. Most respondents showed behavioral changes in consumption that aligned with a low-purine diet and increased diet adherence. Low-purine diet counseling is effective in increasing knowledge and dietary patterns in patients with gout arthritis. Therefore, it is recommended to continue implementing this program.